Ako muna A comparative study on the level of self-centeredness between working and non-working college students. - Encina, Arianne (Tacloban City Arianne Encina, Gellian Eve Ong [and] Joanne Grace Rayos, 2010)
This study was made to investigate the level of self-centeredness between working and non-working college students. The quantitative and qualitative method of research was utilized. The investigation was conducted in the UP Visayas Tacloban College, Leyte Normal University and Eastern Visayas State University. The sampling technique used were convenient and purposive sampling and it comprised 100 college students. Data was gathered using the 14-item survey questionnaire. Moreover, 20% of the respondents' sample was interviewed. Data were presented, analyzed and interpreted through tables, frequencies, and t-test. Results revealed that no significant difference was found to exist in the level of self-centeredness between working and non-working students. In the light of the above findings, the researchers concluded that majority of the respondents whether working or not, possess a low level of self-centeredness. It is therefore recommended that further studies be concluded focusing to other groups of individual from different age brackets.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science